Discover new perspectives and gain insights with IDNLearn.com. Our Q&A platform offers reliable and thorough answers to help you make informed decisions quickly and easily.
Sagot :
To make [tex]\(x\)[/tex] the subject of the formula [tex]\(S = w \sqrt{a^2 - x^2}\)[/tex], we need to isolate [tex]\(x\)[/tex] on one side of the equation. Here are the steps to achieve this:
1. Starting equation:
[tex]\[ S = w \sqrt{a^2 - x^2} \][/tex]
2. Isolate the square root term: Divide both sides by [tex]\(w\)[/tex]:
[tex]\[ \frac{S}{w} = \sqrt{a^2 - x^2} \][/tex]
3. Eliminate the square root: Square both sides to get rid of the square root:
[tex]\[ \left(\frac{S}{w}\right)^2 = a^2 - x^2 \][/tex]
This simplifies to:
[tex]\[ \frac{S^2}{w^2} = a^2 - x^2 \][/tex]
4. Rearrange to isolate [tex]\(x^2\)[/tex]: Move [tex]\(x^2\)[/tex] to one side and [tex]\(\frac{S^2}{w^2}\)[/tex] to the other side:
[tex]\[ x^2 = a^2 - \frac{S^2}{w^2} \][/tex]
5. Solve for [tex]\(x\)[/tex]: Take the square root of both sides to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \pm \sqrt{a^2 - \frac{S^2}{w^2}} \][/tex]
Thus, the solutions for [tex]\(x\)[/tex] are:
[tex]\[ x = \sqrt{a^2 - \frac{S^2}{w^2}} \quad \text{and} \quad x = -\sqrt{a^2 - \frac{S^2}{w^2}} \][/tex]
So, the values of [tex]\(x\)[/tex] in terms of [tex]\(S\)[/tex], [tex]\(w\)[/tex], and [tex]\(a\)[/tex] are:
[tex]\[ x = \pm \sqrt{a^2 - \frac{S^2}{w^2}} \][/tex]
or, more explicitly,
[tex]\[ x = \sqrt{a^2 - \frac{S^2}{w^2}} \quad \text{or} \quad x = -\sqrt{a^2 - \frac{S^2}{w^2}} \][/tex]
These are the two possible solutions for [tex]\(x\)[/tex].
1. Starting equation:
[tex]\[ S = w \sqrt{a^2 - x^2} \][/tex]
2. Isolate the square root term: Divide both sides by [tex]\(w\)[/tex]:
[tex]\[ \frac{S}{w} = \sqrt{a^2 - x^2} \][/tex]
3. Eliminate the square root: Square both sides to get rid of the square root:
[tex]\[ \left(\frac{S}{w}\right)^2 = a^2 - x^2 \][/tex]
This simplifies to:
[tex]\[ \frac{S^2}{w^2} = a^2 - x^2 \][/tex]
4. Rearrange to isolate [tex]\(x^2\)[/tex]: Move [tex]\(x^2\)[/tex] to one side and [tex]\(\frac{S^2}{w^2}\)[/tex] to the other side:
[tex]\[ x^2 = a^2 - \frac{S^2}{w^2} \][/tex]
5. Solve for [tex]\(x\)[/tex]: Take the square root of both sides to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \pm \sqrt{a^2 - \frac{S^2}{w^2}} \][/tex]
Thus, the solutions for [tex]\(x\)[/tex] are:
[tex]\[ x = \sqrt{a^2 - \frac{S^2}{w^2}} \quad \text{and} \quad x = -\sqrt{a^2 - \frac{S^2}{w^2}} \][/tex]
So, the values of [tex]\(x\)[/tex] in terms of [tex]\(S\)[/tex], [tex]\(w\)[/tex], and [tex]\(a\)[/tex] are:
[tex]\[ x = \pm \sqrt{a^2 - \frac{S^2}{w^2}} \][/tex]
or, more explicitly,
[tex]\[ x = \sqrt{a^2 - \frac{S^2}{w^2}} \quad \text{or} \quad x = -\sqrt{a^2 - \frac{S^2}{w^2}} \][/tex]
These are the two possible solutions for [tex]\(x\)[/tex].
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. For trustworthy and accurate answers, visit IDNLearn.com. Thanks for stopping by, and see you next time for more solutions.